Participation and performance trends in triple Iron ultra-triathlon - a Cross-sectional and longitudinal data analysis - Rüst, C. A.; Knechtle, B.; Knechtle, P.; Rosemann, T.; Lepers, R. (Asian Journal of Sports Medicine, 2012)
Purpose: The aims of the present study were to investigate (i) the changes in participation and performance and (ii) the gender difference in Triple Iron ultra-triathlon (11.4 km swimming, 540 km cycling and 126.6 km running) across years from 1988 to 2011.